Kadar Ferritin dengan Status Gizi Pasien Thalassemia β Mayor Anak di RSAM Bandar Lampung - Rita Agustina; Zulhafis Mandala; Rewina Liyola (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Thalassemia is a disease of hemolytic anemia characterized by abnormalities in globin chain synthesis. Continuous transfusion in patients with thalassemia can cause iron buildup or accumulation of iron so that ferritin levels increase in the body, especially in the liver, heart, and endocrine organs. Problems in the endocrine glands and the condition of anemia can interfere with the growth of children, causing a decrease in appetite and cause a lack of nutrition into the body. The purpose of the research is to know the correlation between ferritin levels with nutritional status in Thalassemia patients β Major children. This research uses an analytic observational method with a cross-sectional approach. The subjects in the study were 60 patients. The instrument used was medical record data. The results of statistical analysis using the Chi-Square test showed a p-value of 0.02 (p-value <0.05) which means that there is a relationship between ferritin levels and nutritional status in Thalassemia patients β Major children in Abdul Moeloek Hospital, Bandar Lampung Year 2019. There is a correlation between ferritin levels with nutritional status in patients with Thalassemia β Major children at Abdul Moeloek Hospital in Bandar Lampung in 2019.